Sex, slavery and the trafficked woman: myths and misconceptions about trafficking and its victims - Vijeyarasa, Ramona (Gender in a global/local world, 2016)
Introduction to trafficking and the mainstream -- The main agendas and those behind them -- Legislative approaches to trafficking : the role of the law in challenging or reinforcing myths and misconceptions -- The coerced victim of trafficking -- The uneducated victim of trafficking -- The poor victim of trafficking -- The female victim of trafficking -- The shortcomings of a criminal justice focus -- The voluntary victim, unmet expectations and contractual and labour rights redress -- Conclusion : towards a more inclusive, victim-centred framework.